2021
DOI: 10.3390/ijms222312973
|View full text |Cite
|
Sign up to set email alerts
|

Royal Jelly Protects against Epidermal Stress through Upregulation of the NQO1 Expression

Abstract: Royal jelly (RJ) is secreted by honeybees and has been used as an apitherapy to obtain healthy skin since ancient times. However, the mechanism of the protective effects of RJ against skin aging and skin diseases caused by skin stress and its components have not been clarified. In this study, we attempted to understand the effect of RJ on epidermal function and observed that NAD(P)H quinone dehydrogenase 1 (NQO1) is significantly induced by RJ in keratinocytes. The expression of NQO1 was also increased in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
9
1
2
Order By: Relevance
“…It is important here to mention that the dominant allergens of royal jelly which could present a limitation to the usage of royal jelly as a therapeutic agent are MRJP1 MRJP2 and MRJP3 [ 56 , 57 ]. However, topical application to the skin has not been associated with allergic reactions; on the contrary, as assessed by recent studies, it has been shown to alleviate symptoms of pruritus in a murine model of allergic contact dermatitis [ 58 ], and data from clinical studies have also confirmed that it protects against epidermal stress reactions, through the upregulation of the stress-responsive gene NQO1 [ 59 ], a fact that further supports its anti-aging potential. The present royal jelly delivery system RJDS was further tested for allergens in a formula that contained RJDS as the only active ingredient in a concentration of 1% v / v , according to an EC Reg 1223/2009 and SCCS 1459 compliant analysis and a patch test that confirmed the absence of allergens.…”
Section: Discussionmentioning
confidence: 99%
“…It is important here to mention that the dominant allergens of royal jelly which could present a limitation to the usage of royal jelly as a therapeutic agent are MRJP1 MRJP2 and MRJP3 [ 56 , 57 ]. However, topical application to the skin has not been associated with allergic reactions; on the contrary, as assessed by recent studies, it has been shown to alleviate symptoms of pruritus in a murine model of allergic contact dermatitis [ 58 ], and data from clinical studies have also confirmed that it protects against epidermal stress reactions, through the upregulation of the stress-responsive gene NQO1 [ 59 ], a fact that further supports its anti-aging potential. The present royal jelly delivery system RJDS was further tested for allergens in a formula that contained RJDS as the only active ingredient in a concentration of 1% v / v , according to an EC Reg 1223/2009 and SCCS 1459 compliant analysis and a patch test that confirmed the absence of allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Kwas 10-hydroksydekanowy sprzyja różnicowaniu się keratynocytów naskórka i wpływa na jego funkcję nawilżającą, zmniejsza apoptozę komórek, uodparnia komórki na stres termiczny i oksydacyjny. Dzięki temu zwiększa syntezę kolagenu i pobudza produkcję transformującego czynnika wzrostu β1 w fibroblastach ludzkiej skóry [6,7]. Udowodniono również, że mleczko pszczele pośredniczy w procesie hamowania enzymów katalizujących peroksydację endogennych lipidów oraz w ekspresji genów cytochromu P450, tym samym wzmacniając działanie antyoksydacyjne produktu pszczelego [2].…”
Section: Mleczko Pszczeleunclassified
“…Liczne badania in vitro metodami DPPH, ABTS+, FRAP, ORAC itp. potwierdziły potencjał antyoksydacyjny produktów pszczelich [7]. Mleczko pszczele zwiększa długowieczność komórek i tym samym uodparnia je na stres termiczny i oksydacyjny.…”
Section: Zastosowanie Produktów Pszczelich W Kosmetykachunclassified
“…Duplan et al revealed that 10H2DA activates keratinocyte differentiation, restores skin barrier function, and reduces in ammation, resulting in moisturization of the epidermis [17]. Our previous report also indicated that RJ induces NAD(P)H quinone oxidoreductase 1 (NQO1) expression, thus protecting the epidermis from oxidative stress [12]. However, the effect of RJ on the maintenance of epidermal homeostasis has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…RJ exerts various biological effects, including antibacterial [10], anti-in ammatory [11], antioxidant [12], estrogen-like [13], and anti-aging [14] effects, with minimal side effects. Protease-treated RJ (pRJ), an allergen-free form of RJ whose proteins have been converted to amino acids and peptides, has also been developed and reported to have additional bene ts compared to non-protease-treated RJ (nRJ) [11,15].…”
Section: Introductionmentioning
confidence: 99%